INFLUENCE OF FORCES ACTING ON THE STRAPS OF THE RING SPINNING MACHINE EXHAUST DEVICES ON THE QUALITY OF THE PRODUCT (American Journal of Technology and Applied Sciences, 2023)
In the study of flexible coupling gears and belt conveyors used in various industries, great attention is paid to the forces that arise during their operation. In the strap pairs of the extraction device of spinning machines, forces similar to those arise and their durability depends on the loads that occur in the strap pairs. In the process of operation, strap pairs experience asymmetrical loads, as evidenced by the results of numerous research studies [1,2,3,4].